Cranks, clickbait and cons: on the acceptable use of political engagement platforms - Fenwick McKelvey (Internet Policy Review)
NationBuilder connects voters, politicians, volunteers and staffers in an integrated digital system. Political parties across the globe use it to manage data and campaigns. Unlike most political technology providers, NationBuilder is nonpartisan and sells to anyone. Given recent controversy around political technology, this paper looks for empirical examples of questionable use. Drawing on a 2017 scan of NationBuilder installations globally, the study identifies three questionable uses as: (1) a mobilisation tool for hate or groups targeting cultural or ethnic identities, (2) a profiling tool for deceptive advertising or stealth media, and (3) a fundraising tool for entrepreneurial journalism. These questionable uses may require NationBuilder to revise its ‘Acceptable Usage Policy’ and raises broader questions about the responsibilities of political technology firms to liberal democracy.